Industrial relations and working conditions developments in Europe 2010 - Sweeney, Ben.; Curtarelli, Maurizio; Broughton, Andrea; European Foundation for the improvement of living and working conditions (Λουξεμβούργο : Υπηρεσία Επισήμων Εκδόσεων των Ευρωπαϊκών Κοινοτήτων, 2011)
This report examines the developments in industrial relations and working conditions in 2010 in the 27 EU Member States and Norway. It also considers EU-level industrial relations and working conditions with, given the economic climate, a particular focus on the crisis and responses to it. Previously trends in working conditions and industrial relations were analysed in two separate reports. However, due to the important interdependences between the two areas, developments in working conditions and industrial relations are combined this year for the first time into a single annual report.
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Quality of life -- European Union countries; Hours of labor -- European Union countries; Industrial relations -- European Union countries; Working conditions -- European Union countries; European Union countries -- Social conditions; Electronic books